2007
DOI: 10.1111/j.1475-2743.2007.00105.x
|View full text |Cite
|
Sign up to set email alerts
|

Effects of vertical distribution of soil inorganic nitrogen on root growth and subsequent nitrogen uptake by field vegetable crops

Abstract: Information is needed about root growth and N uptake of crops under different soil conditions to increase nitrogen use efficiency in horticultural production. The purpose of this study was to investigate if differences in vertical distribution of soil nitrogen (N inorg ) affected root growth and N uptake of a variety of horticultural crops. Two field experiments were performed each over 2 years with shallow or deep placement of soil N inorg obtained by management of cover crops. Vegetable crops of leek, potato… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
30
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(33 citation statements)
references
References 28 publications
3
30
0
Order By: Relevance
“…Where comparisons were possible, the root growth of the crops was close to previous results (Kristensen and Thorup-Kristensen, 2007;ThorupKristensen, 2006b). Instead it was the addition of the extra element of fertility building crops and their root growth which so strongly improved the soil exploitation of the O2 system.…”
Section: Reduced Nutrient Losses To the Environmentsupporting
confidence: 57%
“…Where comparisons were possible, the root growth of the crops was close to previous results (Kristensen and Thorup-Kristensen, 2007;ThorupKristensen, 2006b). Instead it was the addition of the extra element of fertility building crops and their root growth which so strongly improved the soil exploitation of the O2 system.…”
Section: Reduced Nutrient Losses To the Environmentsupporting
confidence: 57%
“…This implies that placement of fertilizer plays a role in the roots' ability to acquire nutrients, as shown by Kristensen and Thorup-Kristensen (2007) who distributed soil inorganic N vertically by different management of cover crops. Shallow placement of N favoured N-uptake in shallow-rooted crops while deep placement favoured deep-rooted crops and increased their root depths.…”
Section: Root Growth and Root Functionmentioning
confidence: 98%
“…Root development studies using minirhizotrons have shown a linear relationship between root depth and accumulated temperature (degree days,°C) based on measurements within the 10-90 cm rooting depths (Thorup-Kristensen & Van den Boogaard 1999; Kristensen & Thorup-Kristensen 2007). The average rate of rooting depth was about 0.75 mm per degree day.…”
Section: Root Growth In Carrotsmentioning
confidence: 99%
“…Thus cover crops or weeds can reduce the need for deep rooting in the succeeding crop and may actually directly reduce the root development of crops in deeper soil layers Kristensen and Thorup-Kristensen, 2007). Under Australian conditions, the focus during the transition phase is generally to maximize water storage during the summer fallow period to re-fill the soil profile.…”
Section: Managing Plants During Transitionmentioning
confidence: 99%
“…Most studies have been conducted using very high concentrations and young plants in artificial systems. Cover crop experiments in the field, where cover crops leave the sub-soil with low N content, have demonstrated that roots of crop plants can proliferate when they encounter high levels of residual N remaining in the deep soil layers (Kristensen and Thorup-Kristensen, 2007;Weligama et al, 2010a), but also that rooting depth may be reduced if they encounter deep layers with low N concentrations. Assuming a crop is adequately supplied with N to satisfy healthy root and shoot growth, species or varietal differences in response to deep soil N concentrations are of interest (NK Ytting, unpubl.…”
Section: Factors Influencing Deep Root Growthmentioning
confidence: 99%